The Vertical Profiles of Phytoplankton in Danau Pinang Luar Buluh CinaVillage, Siak Hulu Sub- District, District Kampar, Riau Province - Sudirman Sihombing; Madju Siagian; Clemens Sihotang (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted on the Danau Pinang Luar Buluh Cina Village Siak HuluSubdistrict District Kampar Riau Province in April - Mei 2013 and aims to understand thephytoplankton vertical rofil in the Pinang Luar Lake. There were 3 stations, station 1 isincomingwater area, Station 2 is agencies lake area. Station 3 is end of the lake area. Samplings wereconducted 3 times, once/week.This research aims to determine the vertical profile ofphytoplankton of Danau Pinang Luar.The results showed 24 species of phytoplankton were classified into four classes, namely:Chlorophyceae (11 species), Cyanophyceae (7 species),Bacillariophyceae (5 species), Euglenophyceae (1 species). Average phytoplankton abundancearound 61578 - 495112 cells/l, species diversity index (H ') of phytoplankton around 4,21 - 4,51,uniformity index around 0,87 - 0,93 and dominance index (C) of about 0,046- 0,063. While thewater quality parameters such as temperature of 31°C, the brightness around 65 - 70 cm, a depth ofapproximately 261,7 - 461.7 cm, pH 6, Dissolved Oxygen approximately 2,93 – 6,4 mg/l, free ofcarbon dioxide around 3,96 – 11,88 mg/l, Nitrate around 0,01-0,02 mg/l, Phosphate approximately0,023 mg/l. Based on the abundance of phytoplankton, concluded that Danau Pinang Luar Outerrelatively moderate fertility levels.Keyword : Phytoplankton, Buluh Cina Village, Danau Pinang Luar